2015
DOI: 10.1088/1009-0630/17/6/08
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Mesh Transparency on the Electrical Characteristics of DC Pseudo Discharge

Abstract: A DC pseudo discharge for air has been studied. Air pressure is used in the range between 0.7 Torr and 12 Torr. The breakdown occurs between a plane cathode and a mesh anode at transparencies of 19%, 46%, and 65%. The current-voltage characteristic curves of the discharge, which are measured at different pressures, distances, and mesh transparences, take effect in the region of abnormal glow. The discharge voltage decreases as the air pressure increases, while more voltage is needed to maintain the discharge w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Plasma is defined as , the 'fourth state of matter',is an electrically neutral ionized gas (quasi-neutral) and contains a significant number of free electrically charged particles, these free electrically charged particles make electrically conductive [1]. DC Pseudo Plasma Discharge is a special type of discharge in which the plasma is performed using a bulk cathode and mesh anode, where the discharge (plasma) takes place behind the mesh anode [2][3][4]. Cold (non-thermal) plasma is become one of common technique which used in surface modification of materials specially the textile surface as it is found that most textile materials are heat sensitive polymer [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma is defined as , the 'fourth state of matter',is an electrically neutral ionized gas (quasi-neutral) and contains a significant number of free electrically charged particles, these free electrically charged particles make electrically conductive [1]. DC Pseudo Plasma Discharge is a special type of discharge in which the plasma is performed using a bulk cathode and mesh anode, where the discharge (plasma) takes place behind the mesh anode [2][3][4]. Cold (non-thermal) plasma is become one of common technique which used in surface modification of materials specially the textile surface as it is found that most textile materials are heat sensitive polymer [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In normal GD, the breakdown takes place between the cathode and anode due to the excitation and ionization processes where the current density has constant value. As a result, the normal glow discharge experiment is modulated according to the virtual cathode theory to increase the current density and improve the energetic electrons [7][8][9]. In the modulated system, the diode is constructed from cathode and semi-transparent anode.…”
Section: Introductionmentioning
confidence: 99%